#1**0 **

First of all, act like the < is a =. this helps for the first part. so the equasion would look like 9(2r-5)-3=7r-4

Now simplfy it.

9(2r-5)-3<7r-4

18r-45-3=7r-4

18r-48=7r-4

Now get r on one side.

18r-7r-48=7r-7r-4 r<4 is the answer

11r-48=-4

Get r alone

11r-48+48=-4+48

11r=44 r=4 r<4 Divide and get the answer for r. Now you go back and see if the inequality changes at all (which it doesn't.)

Guest Sep 15, 2017

#1**0 **

Best Answer

First of all, act like the < is a =. this helps for the first part. so the equasion would look like 9(2r-5)-3=7r-4

Now simplfy it.

9(2r-5)-3<7r-4

18r-45-3=7r-4

18r-48=7r-4

Now get r on one side.

18r-7r-48=7r-7r-4 r<4 is the answer

11r-48=-4

Get r alone

11r-48+48=-4+48

11r=44 r=4 r<4 Divide and get the answer for r. Now you go back and see if the inequality changes at all (which it doesn't.)

Guest Sep 15, 2017